KARAKTERISTIK PERPINDAHAN PANAS PADA PENDINGINAN MODEL SUNGKUP REAKTOR AP1000 DENGAN UDARA YANG BERSIRKULASI ALAMIAH - Hermawan, Nanang Triagung Edi; Pasek, Ari Darmawan; Umar, Efrizon (LIPI Press, 2011)
Electric energy demand always grows up. Nuclear energy is one of energies alternative in the future. AP1000 is III+ generation reactor that will possibly built in Indonesia. One of the safety AP1000s features is containment cooling system by natural circulation of air. Experimental study on heat transfer characteristic in containment surface of AP1000 model was done in laboratory scale. From these research, it knows that critical heat fl ux happened at power 2010 watt or 553,47 watt per meter square heat fl ux. Empirical correlation from these research is Nux = 7,086. Rax*0,1906; 2,09 x 106 < Rax* < 1,24 x 1012 for cylindrical concentric part and Nux = 1,308. Rax*0,2527; 7,51 x 105 < Rax* < 7,08 x 1010 for ellipse sector.